Impact of institutional quality on foreign direct investment inflow: Evidence from Croatia - Ljubo Jurčić; Sanja Franc; Antea Barišić (Business Systems Research (BSR), 2020)
Background: Foreign direct investment (FDI) flows are unevenly distributed around the world and determined by different factors. The literature points out to economic and non-economic determinants of FDI flows, while the latter have shown to generate ambiguous effects across regions. Objectives: The primary goal of this paper is to examine the relationship between non-economic determinants and the FDI inflow in Croatia from 1996 to 2017, thus capturing different periods of the economic cycle. The importance of non-economic institutional determinants of FDI is analysed in parallel with the economic determinants. Methods/Approach: This study uses available data on FDI per capita and a set of non-economic (institutional) and economic determinants. We employed the OLS regression analysis to determine the significance of FDI inflow determinants and compare the relevance of non-economic to economic factors. Results: Results of this exploratory study show that institutional quality variables included in the model (regulatory quality, political stability, and government effectiveness, the rule of law and control of corruption) could not be pointed out as important determinants of the FDI inflow in Croatia. Economic variables GDP per capita and average gross wage prove to be important in determining the FDI inflow in Croatia. Conclusions: The research results point to a variety of FDI determinants among countries and economic cycle periods. Given the evidence from Croatia, variations, especially in institutional determinants, might be caused by the diverse FDI inflow characteristics and specificities of receiving economies.
Keywords: F21; F63; 330; economic determinants; foreign direct investment; institutional quality